2022
DOI: 10.1007/s10681-022-03011-1
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction and grain yield stability of drought tolerant cowpea landraces in Ethiopia

Abstract: Cowpea is one of the most important indigenous food and forage legumes in Africa. It serves as a primary source of protein for poor farmers in drought-prone areas of Ethiopia. The crop is used as a source of food, and insurance crop during the dry season. Cowpea is adaptable to a wide range of climatic conditions. Despite this, the productivity of the crop is generally low due to lack of stable and drought tolerant varieties. In this study, 25 cowpea genotypes were evaluated in ve environments using a triple l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
6
13
0
Order By: Relevance
“…Understanding the variation among cowpea genotypes for leaf shape and size could potentially assist breeders in improving the crop for drought tolerance and yield. Previous studies [134] have shown that drought tolerance is associated with small leaf size, while other studies have reported that leaf shape and size are associated with photosynthesis rate and capacity. It has also been reported that leaf shape is not affected by geographic region [135], while other studies [136] have reported the opposite.…”
Section: Conventional Breedingmentioning
confidence: 87%
See 1 more Smart Citation
“…Understanding the variation among cowpea genotypes for leaf shape and size could potentially assist breeders in improving the crop for drought tolerance and yield. Previous studies [134] have shown that drought tolerance is associated with small leaf size, while other studies have reported that leaf shape and size are associated with photosynthesis rate and capacity. It has also been reported that leaf shape is not affected by geographic region [135], while other studies [136] have reported the opposite.…”
Section: Conventional Breedingmentioning
confidence: 87%
“…Several studies have focused on investigating genotype × environment (G × E) interactions and the change in the ranking of cowpea genotypes for seed grain in Egypt [100], Brazil [133], Ethiopia [134], Zimbabwe [135], and South Africa [136][137][138]. Fewer studies [97] have focused on G × E for cowpea yield and nutritional values.…”
Section: Conventional Breedingmentioning
confidence: 99%
“…In cowpea, edaphoclimatic variables such as minimum temperature, solar radiation, rainfall, wind speed, length of crop growth cycle, and altitude can affect the performance of genotypes in different environments (Oliveira et al., 2020). Bear in mind that 100‐grain weight is a quantitative trait, so it is expected that the greatest variation in this trait is due to the environmental effects (Mekonnen et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Cowpea as a dryland legume crop has significant contribution to food and nutritional security in tropical and sub-tropical regions of the world, including in sub-Saharan Africa (SSA) (Dube and Fanadzo, 2013;Mekonnen et al, 2022b). Cowpea often is called "the poor man's meat" as it is a significant and cheap source of protein, minerals, and vitamins for the rural poor who have limited access to protein from animal sources such as meat and fish in SSA communities (Dube and Fanadzo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cowpea often is called "the poor man's meat" as it is a significant and cheap source of protein, minerals, and vitamins for the rural poor who have limited access to protein from animal sources such as meat and fish in SSA communities (Dube and Fanadzo, 2013). It has the ability to grow under harsh environmental conditions where other major crops fail (Timko and Singh, 2008) and is a climate-resilient smart legume crop for food security, especially in SSA (Mekonnen et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%